Poverty and the health of children and adolescents at the end of the COVID-19 pandemic. Results of the KIDA study - Miriam Blume; Elvira Mauz; Mira Tschorn; Kristin Manz; Anja Schienkiewitz; Jennifer Allen; Jens Hoebel; Petra Rattay (Journal of Health Monitoring)
Background: During the COVID-19 pandemic, young people at risk of poverty were particularly affected by contact restrictions as well as by daycare centre and school closures. The aim here is to describe the health status of young people at risk of poverty in comparison to their peers from financially better-off families at the end of the pandemic. Methods: The analyses are based on the data of 3- to 15-year-olds from the study German Children’s Health Update (2022/2023). Prevalences stratified by income were determined for selected indicators of health, health-related behaviour and psychosocial stress and resources. A comparison was made between families at risk of poverty and families with medium and high incomes. Poisson regressions were adjusted for parents’ level of education. Results: Young people at risk of poverty are more likely to have poor health than their peers from financially better-off families. While the former are less likely to participate in organised sport in their leisure time, there are no differences in participation in voluntary sports activities at school according to family income. Conclusions: Strategies to reduce health-related disadvantages for young people at risk of poverty must be implemented at the level of society as a whole and in local settings. Continuous monitoring of children’s and adolescents’ health can help to identify trends at an early stage.